Quality of services to client and of the services of support in the basic unit of family’s health - Barroso, Lea Maria Moura; Victor, Janaína Fonseca (Rev Rene, 2003)
The present work searched to assess through of quality recognition instrument (IRQ), the actions developed in the basic units of family’s health (UBASF), approaching the activies played and the operation of the support’s service the information went in 2002 in october, two UBASF through of the structured observation and the IRQ. The results reveal the UBASF doesn’t reach the aceptable value of quality, according to the methodology of the impovement quality of the basic atetion, however, many factories are related like the capable people in the different areas of attention to client and the improvement of the support’s service.